European report on child injury prevention - Sethi, D. (Dinesh) (World Health Organization, Europe, 2008)
Injuries are a leading cause of death and disability in children. This report presents evidence on how they can be prevented, and calls for greater commitment and action from policy-makers and practitioners to decrease the burden of injuries. Children are particularly vulnerable to injuries, and need special consideration to safeguard their right to health and to a safe environment, free from injury. The evidence base for prevention programmes is presented in this report. Health systems and in particular child health programmes throughout the European Region should prioritize child injury prevention and control.